PENGAMBILAN KEPUTUSAN TOTAL QUALITY MANAGEMENT DALAM RANAH PENDIDIKAN ISLAM - Suherman, Ade (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
Decision making in the implementation of Total Quality Management (TQM) in Islamic education is a crucial aspect that integrates the principles of quality management with Islamic values. TQM emphasizes decision making based on data and facts supported by the participation of all stakeholders through the principle of deliberation. In this study, the researcher will use a qualitative descriptive research type with a library research method that takes data sources from relevant theories in the form of: books, and articles, journals by reviewing various sources of literature. The technique used in this study is the purposive technique in selecting literature, namely by considering the relevance of the content, the credibility of the source, and the currency of the information. The results of this study are that the implementation of Total Quality Management (TQM) in Islamic education has great potential to improve the quality of education as a whole, both in terms of academics and student character development. TQM emphasizes continuous improvement, empowerment of human resources, and data-based decision making.